Association between nutritional status and socio-economic status among school children aged 9-17 years in a semi-urban area of Nepal - Sophie Amalie Hamann; Lene Thorup; Cecilie Blenstrup Patsche; Lena Hohwü; Vibeke Elisabeth Hjortdal; Bishal Gyawali; Dinesh Neupane; Per Kallestrup (BMC, 2023)
Abstract Background In many low-and middle-income countries (LMICs), childhood overweight is increasing, while underweight remains a problem. This study aimed to investigate the association between socio-economic status (SES) and nutritional status among Nepalese school children. Methods This cross-sectional study used a multistage random cluster sampling method and included 868 students aged 9-17 years from both public and private schools located in a semi-urban area of Pokhara Metropolitan City, Nepal. SES was determined based on a self-reported questionnaire. Body weight and height were measured by health professionals and body mass index (BMI) was categorized based on the World Health Organization BMI-for-age cut-offs. The association between Lower and Upper SES and BMI was assessed using mixed-effects logistic regression model estimating the adjusted odds ratio (aOR) with a corresponding 95% confidence interval (CI) and compared to Middle SES. Results The proportion of obesity, overweight, underweight, and stunting among school children was 4%, 12%, 7%, and 17%, respectively. More girls were overweight/obese compared with boys (20% vs. 13%). The mixed-effects logistic regression model showed that both participants from Lower SES households and Upper SES households had a higher tendency to be overweight compared to participants from Middle SES; aOR = 1.4; 95% CI 0.7-3.1 and aOR = 1.1; 95% CI 0.6-2.1, respectively. Furthermore, stunting and overweight occurred simultaneously. Conclusions This study found that about one out of four children and adolescents in the study setting was malnourished. There was a tendency that both participants from Lower SES and Upper SES had higher odds of being overweight compared to participants from Middle SES. Furthermore, both stunting and overweight were present simultaneously in some individuals. This emphasizes the complexity and importance of awareness of childhood malnutrition in LMICs like Nepal.